The Urgency of Tolerance and Peace Values in The Educational Environment of Mahad Al-Zaytun - Rohmah, Siti Ngainnur; Islami, Bilat Nur; Nurmadhani, Wilda; Haekal, Muhammad; Roiddin, Farhan; Sidiq, Kholaif Aulia; Arrasyid, Muhammad Ikhwan; Fadillah, Muhammad Haikal (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
The Indonesian state with its various cultures has millions of endemic characteristics in every corner. Starting from the diversity of languages, cultures, to religions and beliefs, Indonesia is an example of the unity of all diversity in unity. At least that's the dream contained in "Bhinneka Tunggal Ika" which is tied to the Garuda's legs. The purpose of this research is to find out the urgency of the value of tolerance and peace in the scope of education in Ma'had Al-Zaytun. This research method is a literature study research, which is a research method that collects, analyzes, and studies written sources that are relevant to the research topic or problem. The process of conducting an overview of previously published literature works related to various topics. The result of this study is that the urgency of the values of tolerance and peace in the scope of education in Ma'had Al-Zaytun is very important and these values of tolerance have been applied through education.Keywords: Urgency; Tolerance; Education